2017
DOI: 10.1123/ijatt.2016-0035
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of the Landing Error Scoring System to Detect Changes in Landing Mechanics: A Critically Appraised Topic

Abstract: Clinical Question:Is there evidence to suggest that the Landing Error Scoring System (LESS) is able to detect functional changes in landing mechanics in healthy individuals after participation in an injury prevention program (IPP)?Clinical Bottom Line:In a healthy, physically active population, there is strong evidence to support the use of the LESS as an outcome measure for changes in landing mechanics after the implementation of IPPs. Clinicians should consider the LESS as an evaluative tool for measuring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the LESS, lower scores should reflect a reduction in injury risk and high injury-risk movement patterns. The LESS was previously addressed in critically appraised topics 32,44,47 and literature reviews 4,7,19,34,48 ; however, no systematic review has critically appraised and summarized research on its psychometrics properties (reliability and validity). Such a systematic review is warranted to ensure the justified use of the LESS in large-scale screening initiatives, monitoring changes in risk factors, establishing the effects of injury prevention programs, and identifying athletes at high risk of injuries.…”
mentioning
confidence: 99%
“…In the LESS, lower scores should reflect a reduction in injury risk and high injury-risk movement patterns. The LESS was previously addressed in critically appraised topics 32,44,47 and literature reviews 4,7,19,34,48 ; however, no systematic review has critically appraised and summarized research on its psychometrics properties (reliability and validity). Such a systematic review is warranted to ensure the justified use of the LESS in large-scale screening initiatives, monitoring changes in risk factors, establishing the effects of injury prevention programs, and identifying athletes at high risk of injuries.…”
mentioning
confidence: 99%
“…Previous research has indicated that the minimal clinically important difference (MCID) for the LESS is approximately 1.16 [ 40 ]. In our study, the pre–post difference in the LESS scores in the sham taping group following the fatigue protocol was 1.12, which is very close to the MCID.…”
Section: Discussionmentioning
confidence: 99%
“…We found that applying dynamic tape decreased the faulty landing strategy by an average of 0.64 errors (14.8% lower) in all volleyball athletes, and the effect of dynamic taping was more prominent in the female athletes (effect size: 1.07). Moreover, previous research showed that the minimal clinical important difference (MCID) of LESS is around 1.16 [ 28 ]. In the current study, the effect of dynamic taping in the high-risk group (LESS ≥ 6) also reached close to the MCID.…”
Section: Discussionmentioning
confidence: 99%